A Multi-Biochemical and In Silico Study on Anti-Enzymatic Actions of Pyroglutamic Acid against PDE-5, ACE, and Urease Using Various Analytical Techniques: Unexplored Pharmacological Properties and Cytotoxicity Evaluation - Šudomová, Miroslava; Hassan, Sherif T S; Khan, Haroon; Rasekhian, Mahsa; Nabavi, Seyed Mohammad (Biomolecules, 2019)
In the current study, pyroglutamic acid (pGlu), a natural amino acid derivative, has efficiently inhibited the catalytic activities of three important enzymes, namely: Human recombinant phosphodiesterase-5A1 (PDE5A1), human angiotensin-converting enzyme (ACE), and urease. These enzymes were reported to be associated with several important clinical conditions in humans. Radioactivity-based assay, spectrophotometric-based assay, and an Electrospray Ionization-Mass Spectrometry-based method were employed to ascertain the inhibitory actions of pGlu against PDE5A1, ACE, and urease, respectively. The results unveiled that pGlu potently suppressed the activity of PDE5A1 (half-maximal inhibitory concentration; IC50 = 5.23 µM) compared with that of standard drug sildenafil citrate (IC50 = 7.14 µM). Moreover, pGlu at a concentration of 20 µg/mL was found to efficiently inhibit human ACE with 98.2% inhibition compared with that of standard captopril (99.6%; 20 µg/mL). The urease-catalyzed reaction was also remarkably inactivated by pGlu and standard acetohydroxamic acid with IC50 values of 1.8 and 3.9 µM, respectively. Remarkably, the outcome of in vitro cytotoxicity assay did not reveal any significant cytotoxic properties of pGlu against human cervical carcinoma cells and normal human fetal lung fibroblast cells. In addition to in vitro assays, molecular docking analyses were performed to corroborate the outcomes of in vitro results with predicted structure-activity relationships. In conclusion, pGlu could be presented as a natural and multifunctional agent with promising applications in the treatment of some ailments connected with the above-mentioned anti-enzymatic properties.
Keywords: kaptopril; Recombinant Proteins; viabilita buněk; Cell Line; Peptidyl-Dipeptidase A; vazebná místa; Protein Structure, Tertiary; Structure-Activity Relationship; terciární struktura proteinů; Sildenafil Citrate; Cell Survival; cyklické nukleotidfosfodiesterasy, typ 5; Molecular Docking Simulation; angiotensin konvertující enzym; Inhibitory Concentration 50; Hydroxamic Acids; ureasa; vztahy mezi strukturou a aktivitou; kyselina pyrrolidonkarboxylová; simulace molekulového dockingu; rekombinantní proteiny; Binding Sites; Pyrrolidonecarboxylic Acid; Urease; lidé; Cyclic Nucleotide Phosphodiesterases, Type 5; Humans; Spectrometry, Mass, Electrospray Ionization; sildenafil citrát; kyseliny hydroxamové; buněčné linie; spektrofotometrie; Captopril; hmotnostní spektrometrie s elektrosprejovou ionizací; Spectrophotometry; inhibiční koncentrace 50